Highlighting the effect of the support during H2S adsorption at low temperature over composite Zn-Cu sorbents. (1st June 2018) - Cimino, S.; Lisi, L.; de Falco, G.; Montagnaro, F.; Balsamo, M.; Erto, A.
Abstract: Reactive adsorption of hydrogen sulphide (H2 S) from gaseous streams at room temperature with mixed Zn and Cu active phase supported onto γ-alumina is dealt in this manuscript. Sorbents with a fixed total metal content and variable Cu:Zn ratios were prepared by impregnation of commercial γ-alumina spheres in order to investigate the role of the support and the possible synergic effect between the two metals on the adsorption mechanism and performance. H2 S (500–3000 ppmv in N2 ) removal tests were run under dynamic conditions at 30 °C. Experimental techniques such as BET and pore size distribution by N2 -adsorption, SEM-EDX, XRD and DRIFT analysis were coupled for the characterization of fresh and spent sorbents. TPD/TPO experiments on saturated sorbents were performed to assess their regenerability and allowed the speciation of adsorbed sulphur species, testifying the complexity of the surface reactions and the effect of the support.